Is this in my contract?: How part-time contract faculty face barriers to reporting academic integrity breaches (Canadian Perspectives on Academic Integrity, 2019)
A holistic approach to academic integrity in higher education requires a concerted and integrated effort of all stakeholders across campus, yet the tiered faculty system of most institutions may be at odds with comprehensive approaches. This paper explores how part-time contract faculty (also known as “sessionals” in Canada) face barriers to reporting student breaches of academic integrity. Drawing on scholarly literature, as well as my experiences as a sessional instructor, I explore this topic. In particular, I note that the time commitment and emotional investment involved in reporting transgressions according to institutional protocol can be especially burdensome for part-time instructors. I conclude with recommendations to better support sessional instructors to foster academic integrity.